การเปิดรับข่าวสาร ความรู้ ทัศนคติ ของประชาชนในเขตกรุงเทพมหานครเกี่ยวกับการคุ้มครองผู้บริโภคของสำนักงานคณะกรรมการคุ้มครองผู้บริโภค - ภัควดี ทั่วจบ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purposes of this research was to study the correlation among Bangkok residents media exposure, knowledge and attitude towards consumer protection of the Office of the Consumer Protection Board. Questionnaires were used to collect the data from 400 samples Frequency, Percentage, Mean, T-test, One-way Analysis of Variance, Standard Deviation and Pearson’s Product Moment Correlation Coefficient were employed for the analysis of the data, SPSS for Windows Program was used for data processing. The results of the study were as follows: 1.There was no difference in the information response about the consumer protection of the Office of the Consumer Protection Board among different demographic characteristic. 2.Difference in demographic characteristic resulted in difference of knowledge about the consumer protection of the Office of the Consumer Protection Board. 3.Different demographic characteristic resulted in difference of attitude toward the consumer protection of the Office of the Consumer Protection Board. 4..Media exposure to the information about the consumer protection did not correlated with knowledge of the consumer protection of Office of the Consumer Protection Board. 5.Media Exposure to information about the consumer protection of the Office of the Consumer Protection Board. 6. Media Exposure to the information about the consumer protection of the Office of the Consumer Protection Board did not correlate with attitude towards the consumer protection of the Office of the Consumer Protection Board.